Comissões de heteroidentificação na UFMT como efetivação do direito fundamental à igualdade - Silva, Guilherme Matheus da (2023)
Policies of affirmative actions are based on the equality principle. They are a set of special political measures to assist victims of past and current group discrimination and social exclusion. In the case of admission processes in public universities, Brazilian’s legal framework warrants to the candidates unlimited and complete consummation of the national policies to promote racial equality while also assuring legal institutional security. In this sense, Hetero-identification Committees were created to inhibit fraud and safeguard admission processes from false racial self-declarations that would benefit candidates who do not have the right to affirmative actions targeted at black people. This research critically evaluates the feasibility of hetero-identification committees as legal instruments in promoting the fundamental right to equality, focused on the admission of black people at the Universidade Federal de Mato Grosso (UFMT). The endeavor was a critical analysis intended to obtain a theoretical and conceptual framework. It was carried out through a bibliographical (theory) and documental (laws, public notices, regulatory guidelines, and jurisprudence analysis) survey. In the end, it confirmed the hypothesis that hetero-identification committees are legitimate instruments for the promotion of the equality principle in the context of admission processes at UFMT because these committees emphasize the inclusive aspect of affirmative actions by warranting that those who receive the benefit, in fact, have the right to it, i.e., black people in the context of this research.